ANALISIS BERPIKIR LOGIS SISWA DALAM MENYELESAIKAN MATEMATIKA REALISTIK DITINJAU DARI KECERDASAN INTERPERSONAL - Asti Faradina; Mohammad Mukhlis (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
This research was motivated by a variety of intelligence possessed by each individual. Where later intelligence was used to solve problems. The one intelligence that can be used in this study was interpersonal. This study aims to describe students' logical thinking in solving realistic mathematical problems in terms of interpersonal intelligence aspects of social sensitivity, social insight, and social communication, especially in mathematics subject matter in the Three Variable Linear Equation System (SPLTV). This research was descriptive. The subjects in this study were three students who had each of the aspects of interpersonal intelligence. Data collection in this study was a questionnaire or questionnaire, tests to solve realistic mathematical problems, interviews, observations, and documentation. Analysis of the data used was the model of Miles, Huberman, and Saldana through three stages including data condensation, data presentation, and conclusions. The validity of the data used triangulation techniques. The results obtained were students who had interpersonal intelligence aspects of social sensitivity meet one indicator of logical thinking and meet two indicators of problem-solving based on Polya's steps but still lacking. Students who had interpersonal intelligence aspects of social insight meet two indicators of logical thinking and can meet three indicators of problem-solving based on Polya's steps but still lacking. Students who had interpersonal intelligence aspects of social communication met all indicators of logical thinking while being able to meet all indicators of problem-solving.